Efficiency of rice farming in flood-prone areas of East Java, Indonesia - Ramadani Suci Warda; Antriyandarti Ernoiz; Qonita Raden Rara Aulia (Open Agriculture, 2024)
Improving rice production by increasing the efficiency of rice farming becomes the alternative strategy in Java Island, where half of the Indonesian populations live. Even though some areas are flood-prone, East Java Province is one of the leading rice producers in Indonesia. This study aims to estimate the level of technical efficiency in rice farming in flood-prone areas in East Java and some socio-economic factors that influence the efficiency. The efficiency of rice farming in this study was analyzed using a stochastic frontier production function approach. The results showed that rice farming in flood-prone areas in East Java has been efficient, with an average efficiency of 76.05%. The estimated parameters of farm size, labor, seed, urea fertilizer, and ZA fertilizer are positively significant to rice production, while tractor use is negatively significant to rice production. In addition, farm size, age of household head (HH), education of HH, land ownership, and off-farm jobs positively influence the efficiency of rice farming.